Pandemic pricing: Evidence from German grocery e-commerce - Svetlana Fedoseeva; Ellen Van Droogenbroeck (Agribusiness, 2023)
The sudden demand spike for online grocery purchases during the Covid-19 pandemic and supply bottlenecks caused by disrupted global value chains put immense pressure on prices. We analyze the prices of the largest German online grocers to test how these challenges affected prices during the first wave of the pandemic. Using a large dataset of online price quotes, we shed light on the magnitude of price changes across retailer types, product categories, and stages of the pandemic. We show that online prices went up as the intensity of Covid-19 containment measures increased. The magnitude of price increases was heterogeneous across retailers and product categories: pure online retailers showed a lower price response compared to hybrid stores, while the prices of essential food items such as baby foods and pantry products increased more than those of other product categories or beverages. [EconLit Citations: E31, Q31].
Keywords: 630; Covid-19; e-commerce; food prices; Germany; retailing